PEMBIAYAAN DAN MANAJEMEN FINANSIAL DI PERGURUAN TINGGI SWASTA - Sonny Muhammad Ikhsan Mangkuwi; Nurjanah Nurjanah; Rahyuni Rahyuni; Risna Purwanti (CV. Adiba Aisha Amira, 2025)
Financing and financial management in private universities are important factors in ensuring the quality and sustainability of education. One of the biggest problems facing society is the high cost of education. The purpose of this study is to examine financial management procedures in private universities (PTS) in Samarinda and to determine methods for improving financial sustainability. A qualitative approach using case studies from several PTS institutions was employed as the methodology. Information was collected through stakeholder interviews, document analysis, and direct observation of financial practices. Based on the research findings, the main issues faced by PTS include excessive reliance on tuition fees, operational inefficiency, and lack of income diversification. Information technology for financial management is still underutilised, which can hinder accountability and transparency. Additionally, the absence of long-term financial planning makes sustainability and efficiency difficult to achieve. Income diversification strategies include optimising expenditures, enhancing transparency in integrated financial management systems, and securing research funds and industry alliances. To facilitate the implementation of these policies, the financial sector also prioritises human resource development. Collaboration between private universities, the government, the business sector, and alumni is crucial in efforts to improve educational standards and ensure long-term sustainability. The development of policies supporting diversification of funding sources, financial technology advancement, and budget management efficiency is expected to enhance access to inclusive and quality higher education.